CORPORATE GOVERNANCE AND INTELLECTUAL CAPITAL DISCLOSURE OF QUOTED NON-FINANCIAL FIRMS IN NIGERIA - Oghoro, Rose Chioma; Edirin, Jeroh (International Journal of Management and Allied Research (IJMAR), 2025)
This study examined the relationship between corporate governance variables and the intellectual capital disclosure of quoted non-financial companies in Nigeria. A multiple linear regression analysis was conducted to ascertain whether intellectual capital disclosure is influenced by corporate governance variables like CEO expertise, audit committee expertise, and board remuneration decisions. The study’s sample consists of non-financial quoted companies in the Nigerian Exchange Group (NGX), comprising the consumer goods sector, the industrial goods sector, the health care sector, the conglomerates sector, and the agricultural sector, and data analyzed span 2021 to 2023. The findings that emanated from the study indicated that CEO expertise and board remuneration practices have a positive and significant influence on intellectual capital disclosure, whereas audit committee expertise exhibited a negative relationship with intellectual capital disclosure. Therefore, this study recommends that companies should prioritize and strengthen CEO expertise by hiring CEOs with strong industry knowledge and experience. In addition, firms should align board remuneration practices with intellectual capital disclosure. Additionally, regulatory bodies should consider introducing market incentives and relevant guidelines/standards that encourage companies to disclose intellectual capital information in corporate reports either mandatorily or voluntarily